(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Cyclical fluctuations in the market economy have been the focus of attention of researchers for many years. Today, the process of reproduction is becoming cyclical, which is a problem of interest of all economic agents. The purpose of the article is to reveal the main causes of economic cycles, their nature and to show the effect of cyclical fluctuations on the production process and employment, as well as in the development of a new socio-economic society as a whole. The article shows the essence of each stage, their disadvantages and advantages, influence on the formation of a creatively developed person.